Pollutant Load Analysis of the Barito River Based on Seasonal Scenarios - Azizah Shalihah A; Asep Sofyan; Suharyanto (Jurnal Serambi Engineering, 2025)
The Barito River is one of the major rivers in Kalimantan Island that plays a strategic role in supporting the social, economic, and environmental aspects of the surrounding communities. However, based on water quality monitoring conducted by the Environmental Agency of Central Kalimantan Province during the years 2021 to 2022 at seven points along the Barito River, it was found that the Water Quality Index indicated a “lightly polluted” status. Residential activities near the river contribute to the pollutant load through direct flow of domestic wastewater into the river. Similarly, the presence of coal stockpiles around the river is also believed to increase the pollution burden. This study aims to predict the water quality conditions resulting from land use activities—particularly residential areas and coal stockpiles—along the Barito River using the Water Quality Analysis Simulation Program (WASP) model. River water quality data was collected at four sampling points. Although the pollutant load carrying capacity from in each segment of the Barito River has not yet been exceeded by the actual pollutant load, the results of the modeling indicate that the concentrations of TSS, BOD, and COD in river water during both the dry and wet seasons have exceeded the water quality standards, with TSS values over 50 mg/L, BOD values above 3 mg/L, and COD concentrations greater than 25 mg/L. Therefore, a strategic management plan for pollution load control is urgently needed to maintain the water quality of the Barito River in accordance with Class II river classification.